Intra-seasonal variability of ball speed and coordination of two team-handball throwing techniques in elite male adolescent players - Serrien, B.; Clijsen, R.; Anders, S.; Goossens, M.; Baeyens, J.-P. (International Journal of Computer Science in Sport, 2016)
In sports biomechanics and motor control, a thorough study of coordination variability is important to understanding how the human movement system is organized. From a more applied sport science perspective, knowledge about performance variability is essential regarding the evaluation of true sport specific effects of any intervention. While there are many reports of intervention studies in team-handball, no description of the amount of normal variability is available. This study investigated variability of two important throwing techniques in team-handball within elite junior players over a 4-month period during a competitive season. To evaluate ball speed variability, the intra-individual coefficient of variation was calculated. The 95th percentile of ball speed variability over all players was 7%, which can be used as an effect size estimate in future research. For coordination variability, a qualitative description based on the output of neural networks was used. All participants presented multiple coordination patterns, representing multi-stability on a month-to-month timescale and switched between stable states without the manipulation of any control variable. Some limitations in the methodology and applications of neural networks in the present study and in biomechanics and motor control in general are highlighted. When more researchers adopt these methodologies, a more coherent framework for their application can emerge.